Triple-band highly sensitive terahertz metamaterial absorber for biomedical sensing applications - Asad Miah; Sams Al Zafir; Md. Hasnain; Joyonta Das; Sayed Muhammad Anowarul Haque; Abdul Wahed (PLoS ONE, 2025)
Due to the growing interest in metamaterials for biomedical applications, this study presents the design and analysis of a novel, compact, triple-band metamaterial absorber for biological sensing in the terahertz range. The structure, with dimensions of 41 × 41 μm2, exhibits exceptionally high absorption rates above 99% at three distinct resonance frequencies of 1.85, 3.62, and 5.63 THz. To validate the design, an equivalent circuit model was created and evaluated alongside electric field, magnetic field, and surface current distributions. A key focus of this work is the sensor’s performance, evaluated by introducing a sensing layer with varying refractive indices. The absorber demonstrates outstanding sensitivity values of 1.5 THz/RIU, 1 THz/RIU, and 0.66 THz/RIU at the third, second, and first resonances, respectively, indicating highly reliable sensing performance across multiple frequency bands. Furthermore, its suitability for biochemical applications was evaluated by testing its ability to detect different samples, such as glucose, malaria, and cervical cancer cells. The absorber also demonstrates strong performance metrics, with a maximum quality factor of 39.13 and a figure of merit (FoM) of 6.95, supporting its reliability. Additionally, its suitability for microwave imaging (MWI) technology is also examined. The combination of near-perfect absorption and high sensitivity makes this compact metamaterial absorber a promising candidate for advanced biomedical sensing and diagnostic technologies.